Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557299
|View full text |Cite
|
Sign up to set email alerts
|

Social fabric fitness

Abstract: Group exercise has multiple benefits including greater adherence to fitness regimens, increased enjoyment among participants, and enhanced workout intensity. While a large number of technology tools have emerged to support realtime feedback of individual performance, tools to support group fitness are limited. In this paper, we present a set of wearable e-textile displays for running groups called Social Fabric Fitness (SFF). SFF provides a glanceable, shared screen on the back of the wearer's shirt to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Work by Mauriello et al [33] evaluated a wearable e-textile display with various runners (n=52). The authors reported that their cohort also favored wearable devices by Garmin.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Mauriello et al [33] evaluated a wearable e-textile display with various runners (n=52). The authors reported that their cohort also favored wearable devices by Garmin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing attention that HCI granted to the sports domain [Ishii et al 1999;Slovák et al 2012;Pijnappel and Mueller 2013;Mauriello et al 2014;Mueller and Muirhead 2015;Kosmalla et al 2016], the integration of commercial selftracking technologies into sports practices has received limited attention. With remarkable exceptions [Tholander and Nylander, 2015;Wakefield et al 2014], the impact of the growing availability of instruments for collecting personal data on sports has not yet been widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable technology also enables new forms of interaction and social experience of an individual and a group. For example, openly displaying personal physiological data on an individual's clothes in a running race could yield positive running experience to other runners even without any direct interactions between them [9]. An individual's outfit can be changed and manipulated by others who are not wearing it [8].…”
Section: Social Experience Around Wearablesmentioning
confidence: 99%